Mononeuritis multiplex following immune checkpoint inhibitors in malignant pleural mesothelioma - Farina, Antonio; Escalere, Manon; Dion, Matthias; Moussy, Martin; Pegat, Antoine; Villagrán-García, Macarena; Devic, Perrine; Lamiral, Anaïde; Seyve, Antoine; Aure, Karine; Wang, Adrien; Gorza, Lucas; et al. (Frontiers in Neurology, 2024)
Introduction: Mononeuritis multiplex is frequently related to vasculitic neuropathy and has been reported only sporadically as an adverse event of immune checkpoint inhibitors. Methods: Case series of 3 patients with mononeuritis multiplex -all with mesothelioma-identified in the database of 2 French clinical networks (French reference center for paraneoplastic neurological syndromes, Lyon; OncoNeuroTox, Paris; January 2015-October 2022) set up to collect and investigate n-irAEs on a nationwide level. Results: The 3 patients (male, median age 86 years, range 72-88) had pleural mesothelioma and received 10, 4, and 6 cycles, respectively, of first-line nivolumab plus ipilimumab therapy. Neurological symptoms involved the median nerves in patient 1 and had a more diffuse distribution in the 2 other patients; they were severe (common terminology criteria for adverse events, CTCAE grade 3) in all patients. Nerve conduction studies indicated mononeuritis multiplex in all patients. Peripheral nerve biopsy demonstrated necrotizing vasculitis in patients 1 and 3, marked IgA deposition without inflammatory lesions in patient 2. Immune checkpoint inhibitors were permanently withdrawn, and corticosteroids were administered to all patients, leading to complete symptoms regression (CTCAE grade 0, patient 2) or partial improvement (CTCAE grade 2, patient 1 and 3). During steroids tapering, patient 1 experienced symptoms recurrence and spreading to other nerve territories (CTCAE grade 3); he improved 3 months after rituximab and cyclophosphamide administration. Discussion: We report the occurrence of mononeuritis multiplex, very rare adverse events of immune checkpoint inhibitors, in 3 patients with mesothelioma. Clinicians must be aware of this severe, yet treatable adverse event.